Encountering the Wounded Healer: Parallel Process and Supervision - St. Arnaud, Kevin (Canadian Journal of Counselling and Psychotherapy, 2017)
This article investigates the clinical utility of the parallel process in the context of supervision. By examining trainees’ transference reactions toward their supervisor, the client’s psychological processes can be illuminated and clinical outcomes can be improved. However, exploring these transference reactions may touch upon the trainees’ wounds, as psychological material of both trainee and client may appear in the transference. Through supportive exploration, supervisors can help trainees to become aware of how their wounds may negatively—or positively—influence their work with clients. However, supervisors must be careful to offer their trainees support without functioning as a therapist.